The safety of blinatumomab in pediatric patients with acute lymphoblastic leukemia: A systematic review and meta-analysis - Marrapodi, Maria Maddalena; Mascolo, Annamaria; di Mauro, Gabriella; Mondillo, Gianluca; Pota, Elvira; Rossi, Francesca (Frontiers in Pediatrics, 2022)
Background: Blinatumomab is a bispecific CD19-directed CD3 T-cell engager that has proven efficacy in children with relapsed or refractory B-cell acute lymphoblastic leukemia (ALL). Despite its efficacy, it has also been associated with the development of potentially serious adverse events such as the cytokine release syndrome (CRS) and neurologic events. The present meta-analysis aimed to assess the safety profile of blinatumomab in terms of serious adverse events, CRS, and neurologic events (such as seizure and encephalopathy) in pediatric patients with B-cell ALL. Methods and Findings: A systematic review was conducted in Pubmed up to December 10, 2021 to retain pediatric clinical trials on blinatumomab. A random effect meta-analysis approach was used. This study followed the PRISMA statement. Four out of the 255 initial references were selected, of which 2 were phase 1/2 clinical trials and 2 phase 3 clinical trials. Blinatumomab was associated with a lower risk of serious adverse events (Risk ratio RR, 0.56; 95%CI, 0.32-0.99) and grade ≥ 3 adverse events (RR, 0.79; 95%CI, 0.67-0.93) compared to chemotherapy. No difference in the risk of CRS (RR, 8.37; 95%CI, 0.27-260.97) and seizure (RR, 6.43; 95%CI, 0.79-53.08) was observed between groups, while for encephalopathy a higher risk was associated with blinatumomab compared to chemotherapy (RR, 8.90; 95%CI, 1.08-73.29). Conclusion: Our data support the good safety profile of bliantumomab in treating pediatric patients with B-ALL.